The Co-Evolution of Science and Law in Plant Breeding: Incentives to Innovate and Access to Biological Resources - Campi, Mercedes Maria (2018)
This paper analyses the co-evolution of scientific progress and intellectual property protection in plant breeding and the debates generated in its design and implementation. It relates the institutional history to several problems related with incentives to innovate, appropriability of innovation rents, disclosure and cumulativeness, and diffusion and access to biological resources. We identify three main issues that were fiercely discussed along history: firstly, whether plant varieties and other biological resources could be considered as inventions or simple products of nature, secondly, how to provide incentives to plant breeders without preventing access to innovation and looking upon the contribution of farmers to obtain present improved varieties, and, thirdly, the social cost of generating monopolies in plant breeding and agriculture as food producers. These three issues have shaped the debates and remained controversial until our days. The analysis shows that legal and scientific factors evolved at different paces, resulting in different IPRs systems, and giving raise to several problems.